Costs and returns in Rwandan smallholder agricultural production: Gross margins and profitability analyses - Mugabo, Serge; Warner, James (International Food Policy Research Institute, 2024)
This paper explores crop commercialization among smallholder agricultural households in Rwanda from a cost and revenue perspective to determine profitability at the farm level. We use standard revenue and cost equations to assess the commercial viability of the smallholders. In general, we find that a household’s total crop production creates positive returns even if implicit costs, such as own family labor and fertilizer subsidies, are included. Specifically, over 80 percent of our sample households generated positive economic returns from farming— referred to as demonstrating a positive gross economic margin (GEM). However, if only crop market sales and market input costs are used in the calculations, only 40 percent of agricultural households generated positive returns—referred to as demonstrating a positive gross marketing margin (GMM). Most of the explanation for this difference is that the typical farm household sells only about one-third of its crop production by value. This outcome suggests that many agricultural households continue to focus on cultivating food crops for their own consumption and do not specialize in commercial production. This is to be expected in an economic context where input, credit, and commodity markets are still developing, production decisions are still shaped by high levels of weather and market risk, and production risk management options are limited, among many other factors. The results of this research provide a better understanding of how Rwandan smallholders might move towards higher value production, with the ultimate goal being to increase household revenues and welfare and accelerate the country’s economic transformation.